WATER-BASED LOGIC: THE WATER HERITAGE OF GREATER NANNING AND ITS ROLE IN URBAN AUTHENTICITY - Li, Tiansheng (Journal of Environmental Science and Sustainable Development, 2025)
Water heritage plays a pivotal role in establishing Greater Nanning as a central city in the upper Pearl River basin of southern China. However, this heritage has largely been overlooked due to an urban narrative dominated by land-centrism. This article explores methods to create a comprehensive understanding of the water heritage of Greater Nanning and discusses how it can be integrated into the concept of urban authenticity. It argues that both tangible and intangible water heritages are essential elements to safeguard urban authenticity and promote sustainable cultural development. This study adopts an explanatory sequential mixed-methods design, combining quantitative analysis with qualitative inquiry through data statistics, archival research, cultural mapping, and interviews to systematically examine water heritage’s structure, evolution, and cultural significance in Greater Nanning. Greater Nanning’s 211 tangible and 166 intangible water heritage items, concentrated in six historic and cultural districts, form a dynamic cultural heritage system structured by the logic of water—an essential foundation of the city’s authenticity. However, current conservation practices remain predominantly land-centered, undermining the integrity of this water-based cultural heritage system. This study proposes a water-based logic approach that connects a range of atypical water heritage elements into an integrated system. It reveals their unique value in maintaining urban authenticity through three key aspects: the integrity of the natural environment, the authenticity of cultural elements, and the continuity of cultural values. To sustain urban authenticity in Greater Nanning, this article proposes the 3C intervention strategy—conservation, cognition, and creativity—as a continuous cycle to rebuild the human–water heritage connection: conservation ensures the authenticity and integrity of water heritage, cognition deepens public understanding through education, exhibitions, and experiential activities, and creativity transforms knowledge into innovative practices and reinforces conservation.